Readmission rates among cardiology inpatients with echocardiography abnormalities associated with heart failure. (August 2016) - O' Halloran, L.; McAdam, B.; Morgan, K.; Lewis, C.; Farrell, D.; Doherty, S.; Burke, S.; McGee, H.
Abstract Background Heart failure is a condition associated with significant morbidity. It is caused by structural or functional abnormalities of the heart. Many of these abnormalities if detected and managed early would prevent the onset of heart failure. Aims The aim of this study was to to determine the usefulness of echocardiography as a means of predicting readmission rates. A secondary aim was to profile patients with echocardiography abnormalities. Methods This was a prospective cohort study that followed patients over 36 months. Data were abstracted from the medical records of 76 cardiology patients in a large urban teaching hospital between 1.6.11 and 31.8.14. The outcome of interest was the number of readmissions occurring up to 48 months after discharge. We also aimed to profile these patients in terms of their co-morbidities and their medication history. Results Of those patients who had echocardiography (n = 447), 76 were considered to have a cardiac disorder (HHD, VHD, or LVSD) (n = 29). The mean readmission rate for HHD was 0.82, LVSD 0.62, and HHD 0.98. Patients with HHD were associated with a higher readmission rate of 1.8980 and for LVSD—1.24 times more likely. Those with a cardiac disorder were 13 % more likely to have a readmission within the next 36 months than those without a cardiac disorder. Conclusions A significant proportion of patients were found to have a cardiac disorder related to HF. Echocardiographic abnormalities were shown to be an independent risk factor for readmission.